Nutritional niches of potentially endemic, facultatively anaerobic heterotrophs from an isolated Antarctic terrestrial hydrothermal refugium elucidated through metagenomics - Craig W. Herbold; Stephen E. Noell; Charles K. Lee; Chelsea J. Vickers; Matthew B. Stott; Jonathan A. Eisen; Ian R. McDonald; S. Craig Cary (Environmental Microbiome)
Abstract Background Tramway Ridge, a geothermal Antarctic Specially Protected Area (elevation 3340 m) located near the summit of Mount Erebus, is home to a unique community composed of cosmopolitan surface-associated micro-organisms and abundant, poorly understood subsurface-associated microorganisms. Here, we use shotgun metagenomics to compare the functional capabilities of this community to those found elsewhere on Earth and to infer in situ diversity and metabolic capabilities of abundant subsurface taxa. Results We found that the functional potential in this community is most similar to that found in terrestrial hydrothermal environments (hot springs, sediments) and that the two dominant organisms in the subsurface carry high rates of in situ diversity which was taken as evidence of potential endemicity. They were found to be facultative anaerobic heterotrophs that likely share a pool of nitrogenous organic compounds while specializing in different carbon compounds. Conclusions Metagenomic insights have provided a detailed understanding of the microbe-based ecosystem found in geothermally heated fumaroles at Tramway Ridge. This approach enabled us to compare Tramway Ridge with other microbial systems, identify potentially endemic taxa and elucidate the key metabolic pathways that may enable specific organisms to dominate the ecosystem.